TOKSISITAS SENYAWA BIOAKTIF TUMBUHAN “SIDONDO” (Vitex negundo L.) PADA Spodoptera exigua Hubner dan Plutella xylostella Linnaeus - Burhanuddin Nasir; Sri Anjar Lasmini (Universitas Tadulako, 2008)
The objectives of this study were to evaluate bioactive compound contents of the ”Sidondo” plant (Vitex negundo L.) especially those compound that are potentially used as botanical pesticide and to test the plant extract influence on tested Spodoptera exigua and Plutella xylostella larvae mortality and toxicity. This study was conducted in Plant Protection and Biotecnology Laboratories, Faculty of Agriculture, Tadulako University from March to October 2008. Results of the study indicated that crude extract of the V. negundo could kill both S. exigua and P. xylostella larvae. The highest mortality rate for S. exigua (32%) was found when the plant was extracted with ethanol and for P. xylostella (27%) was seen with methanol extraction. The effective extract concentration was 0.3% for S. exigua and 0.2% for P. xylostella. The extract sub-lethal concentration (LC50) was 0.49% for S. exigua and 0.42% for P. xylostella. The extract of V. negundo contained Saponin which could be used as a botanical insecticide active ingredient